KUALITAS PELAYANAN DALAM MENANGANI PASIEN DI PUSKESMAS PEMBANTU DESA KALUKUBULA DI KECAMATAN SIGI BIROMARU - Yorensia Resti; Wulandari Wulandari; Anang Ma’ruf; Lidia Olivia Balanda; Mustainah; Intam Kurnia; Dandan Haryono (Kampus Akademik Publiser, 2025)
This article discusses the quality of service and treatment of patients at the auxiliary health center, Sigi district, Sigi Biromaru sub-district, this research was carried out at the auxiliary health center in Kalukubula village with the aim of obtaining and providing information and wanting to know how the quality of service is in accordance with standard operational procedures so that through this we can find out the level of community satisfaction with the services provided, This research used qualitative research methods, observation, interviews and documentation, using 5 informants, with the aim of the informants being the employees of the Kalukubula village community health center and the Kalukubula village community. The results of this research indicate that the quality of service is maximum. In this research the author has collected data through interviews and secondary data in the form of documents.